Preparation method of DDR zeolite membrane

By loading DDR zeolite seeds onto a silica fume substrate and using a steam heating method with a strong alkali and a structure-directing agent, a DDR zeolite membrane was prepared, solving the problem of high preparation cost of DDR zeolite membranes and achieving efficient CO2 separation and improved mechanical strength.

CN119258810APending Publication Date: 2025-01-07CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411704668.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing DDR zeolite membranes are expensive to prepare, and the porous Al2O3 support used is also expensive, making it difficult to achieve efficient and economical CO2 separation.

Method used

Using silica fume as a carrier, DDR zeolite films are prepared by loading DDR zeolite seeds and combining them with strong alkali and structure guiding agents, and by using steam heating and calcination processes. The seed loading, hydrothermal reaction time and temperature are controlled to form DDR crystals.

Benefits of technology

The preparation cost of DDR zeolite membrane was reduced, the mechanical strength of the membrane was improved, cracking during calcination was reduced, and a highly efficient CO2 separation effect was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258810A_ABST
    Figure CN119258810A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a DDR zeolite membrane, and belongs to the field of zeolite molecular sieve membrane preparation. The invention provides a preparation method of a DDR zeolite membrane, which comprises the following steps: (1) loading a DDR zeolite seed crystal on the surface of a silica fume matrix, and sintering to obtain a shrinkage-state silica fume matrix loaded with the seed crystal; and (2) loading strong base and a structure-directing agent on the surface of the shrinkage-state silica fume matrix, and then carrying out steam heating to obtain the DDR zeolite membrane, the temperature of steam heating is 145 to 175 DEG C. SiO2 in the silica fume has high reaction activity, and the original structure is destroyed to form free Si ions and free O ions under the conditions of strong base and steam. Free Si ions and free O ions are rearranged and combined under the action of the structure-directing agent and the DDR zeolite seed crystal on the surface to form a three-dimensional space net structure taking a silica tetrahedron as a main component to generate DDR crystals, and the DDR zeolite membrane is obtained through growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of zeolite molecular sieve membrane preparation, and in particular to a method for preparing a DDR zeolite membrane. Background Art

[0002] Climate change is a global problem. At present, the carbon dioxide emissions from countries around the world are increasing, which has a serious negative impact on the global greenhouse effect. Emerging technologies are urgently needed to separate, collect and reuse the emitted carbon dioxide.

[0003] Membrane adsorption separation technology is one of the most effective technologies for capturing various industrial exhaust gases and has been favored by researchers. 2 The molecular diameter of CO 2 Separation from other gases, especially CO 2 / CH 4 Mixed gas makes DDR type zeolite membrane become CO 2 One of the ideal separation materials.

[0004] At present, pure chemical reagents such as silica sol are mostly used in the synthesis of DDR zeolite molecular sieve membranes, which are expensive and basically use porous Al 2 O 3 Carrier, high price. Summary of the invention

[0005] The invention provides a method for preparing a DDR zeolite membrane. The DDR zeolite membrane prepared by the invention has low cost.

[0006] The present invention provides a method for preparing a DDR zeolite membrane, comprising the following steps:

[0007] (1) loading DDR zeolite seed crystals on the surface of a silica fume matrix and then sintering the matrix to obtain a shrunken silica fume matrix loaded with seed crystals;

[0008] (2) loading a strong base and a structure directing agent on the surface of the shrunken silica fume substrate and then steam heating the substrate to obtain the DDR zeolite membrane;

[0009] The temperature of the steam heating is 145-175°C.

[0010] Preferably, the method for preparing the silica fume matrix comprises: mixing the silica fume and the adhesive solution and then grinding them, and then placing the ground mixture in a mold and flattening it.

[0011] Preferably, in step (1), the mass of the DDR zeolite seed crystals is 1 to 10% of the mass of the silica fume matrix;

[0012] The loading amount of DDR zeolite seeds per unit area of ​​the loaded silica ash matrix is ​​2 to 20 mg / cm 2 .

[0013] Preferably, the sintering includes: a first heating, a first sintering, a second heating, a second sintering and a cooling;

[0014] The first heating rate is 1 to 5°C / min;

[0015] The first sintering temperature is 400-600°C, and the holding time is 0.5-5h;

[0016] The second heating rate is 1 to 10°C / min;

[0017] The second sintering temperature is 700-1100°C, and the holding time is 0.5-5h;

[0018] The cooling rate of the cooling is 1-5°C / min.

[0019] Preferably, in step (1), before sintering after loading, the method further comprises: pressing and molding the silica fume matrix loaded with DDR zeolite seeds obtained by the loading.

[0020] Preferably, the compression molding pressure is 5 to 30 MPa and the time is 1 to 20 min.

[0021] Preferably, the load in step (2) preferably includes:

[0022] The shrunken silica fume matrix loaded with seed crystals is repeatedly immersed in a solution containing a strong base, a structure directing agent and water, taken out and dried.

[0023] Preferably, the number of repetitions is 1 to 5 times.

[0024] The time of each immersion is independently 10 to 60 seconds.

[0025] Preferably, the steam heating comprises: placing the shrunken silica ash matrix loaded with seed crystals, strong base and structure directing agent obtained after the loading in step (2) above a solution containing strong base, structure directing agent and water, heating the mixed solution, and the steam generated by the heating heats the shrunken silica ash matrix loaded with seed crystals, strong base and structure directing agent.

[0026] Preferably, after the steam heating, the method further comprises: calcining the obtained wet membrane and then cooling it to room temperature to obtain the DDR zeolite membrane;

[0027] The calcination temperature is 400-700°C and the holding time is 1-7h;

[0028] The heating rate of heating to the calcination temperature is 1 to 5°C / min;

[0029] The cooling rate is 1-5°C / min.

[0030] SiO in silica fume 2 It has a high reaction shrinkage state. Under the conditions of strong alkali and steam, the original structure is destroyed to form free Si ions and free O ions. Under the action of the structure directing agent and the surface DDR zeolite seeds, the free Si ions and free O ions are rearranged and combined to form a three-dimensional spatial network structure mainly composed of silicon-oxygen tetrahedrons to generate DDR crystals. The generated DDR crystals grow to obtain a DDR zeolite membrane. The results of the embodiment show that the present invention uses silica ash to prepare a zeolite membrane carrier and self-grows a DDR zeolite membrane on its surface, realizing its high added value utilization and reducing the preparation cost of the DDR zeolite membrane.

[0031] Furthermore, the present invention prepares DDR zeolite membranes of different thicknesses by controlling the seed loading amount and the hydrothermal reaction time and temperature.

[0032] Furthermore, the present invention can prepare DDR zeolite with a particle size similar to that of silica fume by controlling the steam heating time, and the difference in thermal expansion coefficient between DDR zeolite membrane and silica fume is smaller than that of Al 2 O 3 Or the SiC support is smaller, which reduces the cracking of the zeolite membrane during calcination to remove the structure directing agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD pattern of the DDR zeolite seed prepared in Example 1;

[0034] Figure 2 The XRD pattern of the self-grown DDR zeolite membrane on the silica fume-based carrier prepared in Example 1;

[0035] Figure 3 This is a surface SEM image of the self-grown DDR zeolite membrane on a silica fume-based carrier prepared in Example 1;

[0036] Figure 4 This is a cross-sectional SEM image of the self-grown DDR zeolite membrane on a silica fume-based carrier prepared in Example 1. DETAILED DESCRIPTION

[0037] The present invention provides a method for preparing a DDR zeolite membrane, comprising the following steps:

[0038] (1) loading DDR zeolite seed crystals on the surface of a silica fume matrix and then sintering the matrix to obtain a shrunken silica fume matrix loaded with seed crystals;

[0039] (2) loading a strong base and a structure directing agent on the surface of the shrunken silica fume substrate and then steam heating the substrate to obtain the DDR zeolite membrane;

[0040] The temperature of the steam heating is 145-175°C.

[0041] The invention loads DDR zeolite crystal seeds on the surface of a silica ash matrix and then sintering is performed to obtain a contracted silica ash matrix loaded with the crystal seeds.

[0042] In the present invention, the method for preparing the silica fume matrix preferably comprises the following steps: mixing the silica fume and the binder solution and then grinding them, and then placing the ground mixture in a mold and flattening it.

[0043] In the present invention, the mass ratio of the silica ash to the adhesive solution is preferably 1:0.01-0.1. In a specific embodiment of the present invention, the mass ratio of the silica ash to the adhesive solution can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09 or 1:0.1; the mass concentration of the adhesive solution is preferably 1-10%; the adhesive in the adhesive solution preferably includes one or more of polyvinyl alcohol carboxyl, methyl cellulose, polyethylene glycol, water glass, paraffin, starch and epoxy resin; the concentration of the adhesive solution is preferably 5wt%.

[0044] The present invention has no special limitation on the grinding, and conventional technical solutions can be used to grind until the product can pass through a 60-mesh sieve.

[0045] The present invention has no particular limitation on the flattening, and conventional means may be used to flatten the upper surface of the ground product.

[0046] In the present invention, the loading method preferably includes: spraying, friction or spin coating;

[0047] The spraying method preferably comprises: mixing DDR zeolite seed crystals with ethanol, spraying the resulting mixture on the surface of the silica fume substrate, and then drying;

[0048] The friction method preferably includes: placing DDR zeolite seeds on fingers and releasing the DDR zeolite seeds by manual friction so that the seeds fall onto the surface of the wollastonite matrix to achieve loading;

[0049] The spin coating method preferably includes: coating a mixture of seed crystals and ethanol on the surface of the wollastonite substrate and then drying it.

[0050] In the present invention, the mass of the DDR zeolite seed crystals is preferably 1-10% of the mass of the silica ash matrix. In a specific embodiment of the present invention, the mass of the DDR zeolite seed crystals can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% of the mass of the silica ash matrix.

[0051] The loading amount of DDR zeolite seeds per unit area on the loaded silica fume matrix is ​​preferably 2 to 20 mg / cm 2 In a specific embodiment of the present invention, the loading amount of DDR zeolite seeds per unit area on the loaded silica ash matrix can be 2 mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 8mg / cm 2 、10mg / cm 2 , 12mg / cm 2 、14mg / cm 2 、16mg / cm 2 、18mg / cm 2 or 20mg / cm 2 .

[0052] Before the sintering, the present invention preferably further comprises: pressing and molding the silica fume matrix loaded with DDR zeolite seeds obtained by the loading.

[0053] In the present invention, the pressing pressure is preferably 5-30 MPa. In a specific embodiment of the present invention, the pressing pressure may be 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa or 30 MPa. The time is preferably 1-20 min. In a specific embodiment of the present invention, the pressing time may be 1 min, 3 min, 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, 17 min, 19 min or 20 min.

[0054] In the present invention, the sintering preferably includes: a first heating, a first sintering, a second heating, a second sintering and a temperature drop;

[0055] The first heating rate is preferably 1-5°C / min. In a specific embodiment of the present invention, the first heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0056] The temperature of the first sintering is preferably 400-600°C. In a specific embodiment of the present invention, the temperature of the first sintering may be 400°C, 450°C, 500°C, 550°C or 600°C. The holding time is 0.5-5h. In a specific embodiment of the present invention, the holding time of the first sintering may be 0.5h, 1h, 2h, 3h, 4h or 5h.

[0057] The second heating rate is 1 to 10°C / min. In a specific embodiment of the present invention, the second heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0058] The temperature of the second sintering is 700-1100°C. In a specific embodiment of the present invention, the temperature of the second sintering can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C. The holding time is 0.5-5h. In a specific embodiment of the present invention, the holding time of the second sintering can be 0.5h, 1h, 2h, 3h, 4h or 5h.

[0059] The cooling rate of the cooling is 1 to 5°C / min. In a specific embodiment of the present invention, the cooling rate of the cooling can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0060] In the present invention, the temperature of the shrunken silica fume matrix loaded with seed crystals is preferably room temperature.

[0061] The sintering process burns the silica ash into a carrier with mechanical strength. During the sintering process, the silica ash particles will partially dissolve to form a liquid that wraps each particle; during the cooling process, sintering necks will be formed between the particles to connect the particles, so that the fired whole forms mechanical strength. This process will cause the silica ash carrier to shrink to a certain extent. Of course, the adhesive will also be removed during the sintering process. This process is in the first sintering process (400-600°C). Sintering can fix the seeds loaded on the surface of the silica ash carrier through the sintering shrinkage of the silica ash carrier.

[0062] After obtaining the shrunken silica fume matrix loaded with seed crystals, the present invention loads a strong base and a structure directing agent on the surface of the shrunken silica fume matrix and then performs steam heating to obtain the DDR zeolite membrane.

[0063] In the present invention, the total mass of the strong base and the structure-directing agent is preferably 15-20% of the mass of the shrunken silica ash matrix loaded with seeds. In a specific embodiment of the present invention, the total mass of the strong base and the structure-directing agent can be 15%, 16%, 17%, 18%, 19% or 20% of the mass of the shrunken silica ash matrix loaded with seeds. In the present invention, the strong base is preferably 5% of the mass of the shrunken silica ash matrix loaded with seeds, and the structure-directing agent is preferably 10% of the mass of the shrunken silica ash matrix loaded with seeds.

[0064] In the present invention, the load preferably includes:

[0065] The shrunken silica fume matrix loaded with seed crystals is repeatedly immersed in a solution containing a strong base, a structure directing agent and water, taken out and dried.

[0066] In the present invention, the number of repetitions is preferably 1 to 5 times. In a specific embodiment of the present invention, the number of repetitions can be 1, 2, 3, 4 or 5 times. The time for each immersion is preferably independently 10 to 60 seconds. In a specific embodiment of the present invention, the time for each immersion can be independently 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds or 60 seconds.

[0067] In the present invention, the mass ratio of water to strong base in the solution is preferably 100:0.2-1. In a specific embodiment of the present invention, the mass ratio of water to strong base in the solution can be 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:0.1; the strong base preferably includes sodium hydroxide.

[0068] In the present invention, the mass ratio of water to the structure directing agent in the solution is preferably 100:0.1-0.5. In a specific embodiment of the present invention, the mass ratio of water to the structure directing agent in the solution can be 100:0.2, 100:0.3, 100:0.4 or 100:0.5; the structure directing agent preferably includes adamantane.

[0069] The present invention has no particular limitation on the drying, and the drying may be performed until there is no obvious water stain on the surface.

[0070] In the present invention, the steam heating preferably comprises:

[0071] The shrunken silica fume matrix loaded with seed crystals, strong base and structure directing agent obtained after the loading is placed above the solution containing strong base, structure directing agent and water, and the mixed solution is heated. The steam generated by the heating heats the shrunken silica fume matrix loaded with seed crystals, strong base and structure directing agent. In addition to providing water vapor, the solution containing strong base, structure directing agent and water will volatilize under heating and adhere to the surface of the silica fume matrix to promote the growth of zeolite membrane.

[0072] In the present invention, the temperature of the steam heating is 145-175°C. In a specific embodiment of the present invention, the temperature of the steam heating can be 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, and the time is preferably 24h, 36h, 48h, 60h, 72h, 84h or 96h.

[0073] In the present invention, after the steam heating, the process further comprises: calcining the obtained wet membrane and then cooling it to room temperature to obtain the DDR zeolite membrane.

[0074] In the present invention, the calcination temperature is 400-700°C. In a specific embodiment of the present invention, the calcination temperature may be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C. The holding time is preferably 1-7h. In a specific embodiment of the present invention, the calcination holding time may be 1h, 2h, 3h, 4h, 5h, 6h or 7h.

[0075] The heating rate of heating to the calcination temperature is preferably 1 to 5°C / min. In a specific embodiment of the present invention, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0076] The cooling rate is preferably 1-5°C / min. In a specific embodiment of the present invention, the cooling rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0077] Calcination removes the structure directing agent.

[0078] The preparation method of the DDR zeolite membrane provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0079] Example 1

[0080] Preparation of DDR zeolite seed crystals: 2g silica ash (components: SiO 2 91.42wt%;Al 2 O 31.47wt%; K 2 O1.03wt%; CaO 0.83wt%; MgO 0.58wt%; Na 2 O 0.45wt%; SO 3 0.25wt%;Cl0.11wt%;Fe 2 O 3 1.01wt%; LOI (volatile matter) 2.85wt%), 1.51g adamantane amine, 0.8g sodium hydroxide, 60g water were mixed and stirred for 5h, then placed in a reactor and reacted at 160°C for 72h, and the product was washed to neutral, filtered and dried.

[0081] Take 1g of silica ash (SiO 2 91.42wt%;Al 2 O 3 1.47wt%; K 2 O 1.03wt%; CaO 0.83wt%; MgO 0.58wt%; Na 2 O 0.45wt%; SO 3 0.25wt%; Cl 0.11wt%; Fe 2 O 3 1.01wt%; LOI (volatile matter) 2.85wt%) and 5wt% polyvinyl alcohol solution were mixed and ground in a mass ratio of 1:0.05 to obtain a mixture that could pass through a 60-mesh sieve. The mixture was placed in a round mold and 0.01g of DDR zeolite seeds were evenly loaded onto the surface of the silica ash (the loading amount of DDR zeolite seeds per unit area was 2mg / cm 2 ), and pressed into shape at 20 MPa, the round tablets were first heated to 550°C at a heating rate of 2°C / min and kept warm for 2 h, then heated to 900°C at a heating rate of 2°C / min and kept warm for 2 h, and finally cooled to room temperature at a cooling rate of 2°C / min to obtain a silica ash-based carrier loaded with DDR zeolite seeds.

[0082] Deionized water, adamantane and sodium hydroxide were mixed and stirred in a molar ratio of 100:0.3:0.6 (60 g of deionized water, 1.51 g of adamantane and 0.8 g of sodium hydroxide) for 5 h to prepare a mother solution.

[0083] The silica ash-based carrier loaded with DDR zeolite seeds was immersed in the mother liquor for 1 minute and then dried. After repeated 3 times, 0.1g of adamantane amine and 0.05g of sodium hydroxide were loaded and placed on a polytetrafluoroethylene platform and placed in a polytetrafluoroethylene reactor. 3g of mother liquor was added to the bottom of the polytetrafluoroethylene reactor to provide steam to avoid direct contact between the carrier and the mother liquor. After reacting in the reactor at a temperature of 160°C for 72 hours, the sample was taken out and soaked in clean water for 30 minutes and then dried. Finally, the temperature was increased to 550°C at a heating rate of 1°C / min, kept for 5 hours, and then cooled to room temperature at a cooling rate of 1°C / min to obtain a silica ash-based carrier self-grown DDR zeolite membrane.

[0084] Figure 1 This is the XRD pattern of the DDR zeolite seed prepared in Example 1.

[0085] Depend on Figure 1 It can be seen that the characteristic peaks of the prepared DDR zeolite seed crystals are obvious, indicating that the prepared DDR zeolite seed crystals have a high degree of crystallization and have the ability to guide crystallization.

[0086] Figure 2 This is the XRD pattern of the self-grown DDR zeolite membrane on a silica fume-based carrier prepared in Example 1.

[0087] Depend on Figure 2 It can be seen that there are obvious characteristic peaks of DDR zeolite, and the amorphous part is the silica fume carrier itself, indicating that DDR zeolite grows on the surface of the silica fume carrier.

[0088] Figure 3 This is a SEM image of the surface of the self-grown DDR zeolite membrane on a silica fume-based carrier prepared in Example 1.

[0089] Depend on Figure 3 It can be seen that a dense DDR zeolite membrane grows on the surface of the silica fume carrier.

[0090] Figure 4 This is the SEM image of the cross section of the self-grown DDR zeolite membrane on the silica fume-based support prepared in Example 1.

[0091] Depend on Figure 4 It can be seen that the cross-section of the self-grown DDR zeolite membrane on the silica fume-based carrier has an obvious stratification phenomenon, the upper layer is a dense DDR zeolite membrane, and the lower layer is a loose and porous silica fume-based carrier.

[0092] Embodiments 2 to 9

[0093] The reaction steps are the same as in Example 1, and the experimental parameters are shown in Table 1.

[0094] Comparative Examples 1 to 9

[0095] The reaction steps are the same as in Example 1, and the experimental parameters are shown in Table 1.

[0096] The products finally obtained from Examples 1 to 9 and Comparative Examples 1 to 9 were subjected to XRD test and SEM observation. The results are shown in Table 2.

[0097] Table 1 Experimental parameters of Examples 1 to 9 and Comparative Examples 1 to 9

[0098]

[0099] Table 2 Product characteristics of Examples 1 to 9 and Comparative Examples 1 to 9

[0100]

[0101]

[0102] As shown in Table 1, Comparative Examples 1 to 3 show that although the silica fume carrier itself has a certain reactivity and can grow DDR zeolite after a long reaction, it is difficult to form a dense DDR zeolite membrane without the guidance of DDR zeolite seeds. Therefore, the surface loading of DDR zeolite seeds is the key to guiding the surface active silicon source of the silica fume carrier to dissolve and crystallize to form a dense DDR zeolite membrane. Examples 1 to 9 and Comparative Examples 6 to 9 also show that the seed reaction temperature is also the key to affecting the quality of the silica fume-based carrier self-grown DDR zeolite membrane.

[0103] Comparative Example 1

[0104] The silica ash-based carrier loaded with DDR zeolite seeds in Example 1 was soaked in a medium mother liquor (60 g of deionized water, 1.51 g of adamantane, and 0.8 g of sodium hydroxide) and then put into a reactor together. After reacting in the reactor at a temperature of 160°C for 72 hours, the sample was taken out and soaked in clean water for 30 minutes and then dried. Finally, the temperature was increased to 550°C at a heating rate of 1°C / min, kept for 5 hours, and then cooled to room temperature at a cooling rate of 1°C / min to obtain a self-grown DDR zeolite membrane on a silica ash-based carrier.

[0105] Although a zeolite film layer can be formed on the surface of the carrier in Comparative Example 1, the carrier directly contacts the strong alkaline mother solution and reacts at high temperature, being dissolved by the strong alkali, destroying the structure, and losing mechanical strength, making it impossible to remove completely (breaking at the touch).

[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a DDR zeolite membrane, characterized in that: The following steps are involved: (1) loading DDR zeolite seed crystals on the surface of a silica fume matrix and then sintering the matrix to obtain a shrunken silica fume matrix loaded with seed crystals; (2) loading a strong base and a structure directing agent on the surface of the shrunken silica fume substrate and then steam heating the substrate to obtain the DDR zeolite membrane; The temperature of the steam heating is 145-175°C.

2. The preparation method according to claim 1, characterized in that: The method for preparing the silica fume matrix comprises: mixing silica fume and an adhesive solution, grinding the mixture, and then placing the mixture obtained by grinding in a mold and flattening the mixture.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass of the DDR zeolite seed crystals is 1 to 10% of the mass of the silica fume matrix; The loading amount of DDR zeolite seeds per unit area of ​​the loaded silica ash matrix is ​​2 to 20 mg / cm 2 .

4. The preparation method according to claim 1, characterized in that: The sintering includes: a first heating, a first sintering, a second heating, a second sintering and a temperature drop; The first heating rate is 1 to 5°C / min; The first sintering temperature is 400-600°C, and the holding time is 0.5-5h; The second heating rate is 1 to 10°C / min; The second sintering temperature is 700-1100°C, and the holding time is 0.5-5h; The cooling rate of the cooling is 1-5°C / min.

5. The preparation method according to claim 1, characterized in that: In step (1), after the loading and before the sintering, the method further comprises: pressing and molding the silica fume matrix loaded with DDR zeolite seeds obtained by the loading.

6. The preparation method according to claim 5, characterized in that: The pressure of the compression molding is 5 to 30 MPa, and the time is 1 to 20 minutes.

7. The preparation method according to claim 1, characterized in that: The load in step (2) includes: The shrunken silica fume matrix loaded with seed crystals is repeatedly immersed in a solution containing a strong base, a structure directing agent and water, taken out and dried.

8. The preparation method according to claim 7, characterized in that: The number of repetitions is 1 to 5 times, and the time of each immersion is independently 10 to 60 seconds.

9. The preparation method according to claim 1, characterized in that: The steam heating comprises: placing the shrunken silica fume matrix loaded with seed crystals, strong base and structure directing agent obtained after the loading in step (2) above a solution containing strong base, structure directing agent and water, heating the mixed solution, and the steam generated by the heating heats the shrunken silica fume matrix loaded with seed crystals, strong base and structure directing agent.

10. The preparation method according to claim 1 or 9, characterized in that: After the steam heating, the method further comprises: calcining the obtained wet membrane and then cooling it to room temperature to obtain the DDR zeolite membrane; The calcination temperature is 400-700°C and the holding time is 1-7h; The heating rate of heating to the calcination temperature is 1 to 5°C / min; The cooling rate is 1-5°C / min.